Analisis Pemborosan pada Proses Produksi Bakery dengan Pendekatan Lean Manufacturing dan FMEA - Narto; Moh. Ismail Hamim; Sutrisno; Mahsun, Moch (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2025)
The goal of this study is to increase the effectiveness of CV. Sinar Mutiara Pangan's donut production process, which is struggling with operational waste. The background of this issue is the removal of non-value-adding tasks in an effort to increase productivity. In order to precisely detect and map waste, the lean manufacturing concept is applied using a number of crucial analysis techniques, including Big Picture Mapping, Pareto diagrams, VALSAT, and FMEA. The analysis's findings show that waiting, needless motion, and overproduction are the three main categories of waste.Waste waiting earned the highest Risk Priority Number (RPN) of 294, making it the highest priority for improvement. The absence of an appropriate scheduling and information integration system, ineffective production space layout, and poor work coordination were the primary fundamental reasons. The overall lead time was reduced by 5,640 seconds, from 17,760 seconds to 12,120 seconds, following the implementation of the suggested changes. A far more efficient production process with less waiting time and a smoother process was achieved by successfully reducing the number of activities from 22 to 15 and eliminating all non-value-added activities for 2,340 seconds to 0 seconds.